Analisis Persepsi Siswa terhadap Model CIRC dalam Pembelajaran Bahasa Indonesia Sekolah Dasar - Merlingga Novianti; Eka Danik Prahastiwi (ARZUSIN, 2026)
Although various cooperative learning models have been widely implemented in Indonesian language learning at the elementary school level, low active engagement and reading comprehension ability among students remain issues that need attention. This study aims to analyze students’ perceptions of the implementation of the Cooperative Integrated Reading and Composition (CIRC) model. This study employed a qualitative approach with a descriptive case study design, involving 20 fourth-grade students and 1 teacher selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed using thematic analysis through the stages of data reduction, data display, and conclusion drawing. The results showed that most students had positive perceptions of the implementation of the CIRC model. Learning was perceived as more interesting, interactive, and helpful in improving reading comprehension through group discussion. In addition, this model also encouraged increased social interaction and students’ active participation. However, this study also found obstacles in the form of unequal participation among group members and difficulties in cooperation at the initial stage of implementation. These findings contribute to strengthening cooperative learning in the context of elementary education while broadening understanding of students’ perceptions of the implementation of the CIRC model in reading instruction. This study concludes that the CIRC model is effective in creating collaborative and meaningful learning, provided that group management is carried out optimally so that learning outcomes can be maximized.